Droysen and the Prussian School of History - Southard, Robert, 1945- (Book collections on Project MUSE., 1995)
The Prussian School of History first predicted and advocated, then celebrated and defended, the unification of Germany by Prussia. Experts in German historiography and the history of German liberalism have often complained about the lack of a book, in any language, that traces the origins and explains the ideas of this school of history. Here is that book. Robert Southard finds that, for the Prussian School, history had an agenda. These historians generally expected history to complete its main tasks in their own time and country. The outcome of their politics was, really, an ""end of history""